Influence of Growth Regulators on Growth, Seed Yield and Qualty of Radish (Raphanus sativus L.) - R. Bala; P. Rattan; A. H. Reddy (International Journal of Economic Plants)
The present investigation was carried out during 2021 at the experimental farm of Faculty of Agricultural Sciences, DAV University, Jalandhar. Radish is an important crop of Punjab region. Use of Plant Growth Regulators is one of the most recent trends in the field of agriculture science. Plant growth regulators are signal molecules, which occurs in plants naturally in very low concentration. In an attempt to find out the influence of growth regulators on growth, seed yield and quality of radish (Raphanus sativus L.) the experiment was planned and executed. It consisted of nine treatments viz., T1 (Control), T2 (GA3 @ 5 ppm), T3 (GA3 @ 10 ppm), T4 (GA3 @ 15 ppm), T5 (GA3 @ 20 ppm), T6 (NAA @ 5 ppm), T7 (NAA @ 10 ppm), T8 (NAA @ 15 ppm), T9 (NAA @ 20 ppm) and was laid in Randomized block design (RBD) with three replications. Punjab Safed Mooli variety was used for the experiment. Observations were recorded on number of leaves per plant, leaf area per plant (cm2), root length (cm), root diameter (cm), root weight (g), fresh weight of plant (g), dry weight of plant (g), plant height (cm), 100 seed weight (g), seed yield plant-1 (g), seed yield plot-1 (g), seed yield ha-1 (q ha-1), TSS (°Brix), ascorbic acid (mg 100 g-1), chlorophyll content (mg 100 g-1) and germination percentage (%). Analysis of variance (ANOVA) revealed significantly differences among treatments for all the characters under study. It was concluded that the application of GA3 @ 20 ppm showed superior performance in all growth, seed yield and quality parameters of radish.